Positioning accuracy of a new image-guided radiotherapy system - Miyabe, Yuki; Sawada, Akira; Takayama, Kenji; Kaneko, Shuji; Mizowaki, Takashi; Kokubo, Masaki; Hiraoka, Masahiro (Medical physics (Lancaster), 2011)
Purpose: To evaluate the accuracy of the patient-positioning function of a newly developed image-guided radiotherapy system, the MHI-TM2000 (Mitsubishi Heavy Industries, Ltd., Japan). Methods: The isocenter positions prescribed by the lasers, MV treatment beam, and image guidance systems (kV X-ray image and kV-CBCT) were calculated using a cube phantom with a 10-mm-diameter steel ball fixed to the center of the phantom. Then, their location discrepancies were estimated. In addition, to verify the scale and orientation of the coordinate axes of the kV X-ray imaging system, positional measurements were repeated with the phantom placed at 50 mm off-isocenter along the vertical, longitudinal, and lateral directions, respectively. Further, image fusions of an anthropomorphic phantom image and the corresponding image translated by a pre-determined amount were performed. Results: The isocenter alignment among the coordinate systems was coincident within 0.5 mm in translation for the vertical, longitudinal, and lateral axes, respectively. The geometrical errors at 50 mm off-isocenter for kV X-ray images and CBCT were within 0.2 mm and 1.0 mm, respectively. The image fusion errors were within 1.0 mm in translation and 1.0° in rotation, respectively. No significant difference in the image fusion accuracy was observed between the chest and pelvis phantoms. Conclusions: The isocenter alignment among the coordinate systems was performed with high accuracy. Furthermore, the automatic image fusion function achieved sufficient patient positioning accuracy and precision for image-guided radiotherapy.